Flipping the English Class Content to Promote Oral Skills in the Classroom (2023)
ABSTRACT: This research study was carried out to determine how implementation of the In-Class Flip approach on student's oral interaction within an eighth-grade classroom at Lola González public school in Medellin. The study was developed with 37 students enrolled in the 802 course. Data collection involved four instruments: teacher journals, a student survey, an observation format, and an interview with the cooperating teacher. This research focused on investigating the effect of the In-Class Flip approach on student interactions, engagement, learning experiences and perceptions. The teacher-researcher's concerns about traditional homework assignments and the need to enhance oral interaction skills were addressed. The findings revealed the benefits of the In-Class Flip approach in enhancing students' oral abilities, fostering interactive and collaborative classroom settings, and empowering students to participate actively in their language learning process.